2021
DOI: 10.1155/2021/2221112
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on Salivary Calcium Levels, Calcium Intake, and Bleeding on Probing in Female

Abstract: Introduction. Smoking is a bad habit that affects both systemic and oral conditions. Nicotine in cigarettes reduces estrogen production that can alter salivary calcium levels. Nicotine also causes vasoconstriction of the gingival blood vessels and decreases gingival bleeding. Low dietary calcium intake is also suspected to influence the low serum calcium levels in smokers. In this study, we evaluated the effect of smoking on salivary calcium levels, calcium intake, and BOP in women. Method. This was an analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Among the smoking population, 16.2% considered as daily smoker with 24.4% smoked factory made-cigarettes. While Tjahajawati et al [16] in Bandung, east Java found out that from 26 female smoker vs. 37 non-smokers aged 18-64 years old, that most of female smokers identified as overweight or obese, 80.8% have a low level educational background and 76.9% were married. Female smokers have a lower calcium level compares to the non-smoking ones.…”
Section: Pingak Et Al [15]mentioning
confidence: 95%
See 2 more Smart Citations
“…Among the smoking population, 16.2% considered as daily smoker with 24.4% smoked factory made-cigarettes. While Tjahajawati et al [16] in Bandung, east Java found out that from 26 female smoker vs. 37 non-smokers aged 18-64 years old, that most of female smokers identified as overweight or obese, 80.8% have a low level educational background and 76.9% were married. Female smokers have a lower calcium level compares to the non-smoking ones.…”
Section: Pingak Et Al [15]mentioning
confidence: 95%
“…In women, smoking causes a lot of health problems, only blood pressure where systolic and diastolic pressures are higher in women who smoke than those who do not smoke. It also causes an increase in blood sugar caused by a decrease in taste sensitivity associated with smoking which will lead to a higher intake of calories, salt and fat [16].…”
Section: Pingak Et Al [15]mentioning
confidence: 99%
See 1 more Smart Citation
“…It may also increase the level of certain pathogens and interfere with neutrophil function, the primary defence against infection, and antibody production [10]. The heat emitted from cigarettes during smoking, and toxins such as nicotine, carbomonoxide and hydrogen cyanide, cause vasoconstriction [11]. Tobacco smoke contains carbon monoxide (CO) which displaces oxygen from haemoglobin [12].…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Systemic disorders, a consequence of smoking, result in even more rapid degeneration of the structures supporting teeth [1,13,14]. Smoking generally leads to delayed tissue healing and therefore renders the regenerative mechanisms of bone and soft tissue less predictable [11,15]. Conversely, quitting smoking slows down the progression of periodontitis and improves treatment response [10,16].…”
Section: Introduction and Objectivesmentioning
confidence: 99%